Decision-making on ILO conventions and recommendations: Legal framework and application - Bernhard Boockmann (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 2000)
The subject of this paper is decision-making on the adoption, ratification and implementation of conventions and recommendations of the International Labour Organisation (lLO). The first part of the paper provides-a brief introduction to the ILO as an international organisation, its treaty base and its most important bodies. In the second part of the paper, we focus on international labour standards. We first explain the decision-making procedure within the ILO which leads to the adoption of conventions and recommendations. We then deal with the ratification of conventions at the national stage and discuss the compliance with the obligations arising from ratification. The focus of the paper is not so much on the formal rules and procedures but on the question of how the rules are applied. Descriptive statistics give evidence on the degree of consensus at the decision-making stage, the voting behaviour of the delegates to the International Labour Conference, the ratification behaviour of member countries, and problems of implementation.
Keywords: 330; Internationale Sozialstandards; Verhandlungen; International; Abstimmung; Public Choice; Welt